FAST Hydrogenations as a Continuous Platform for Green Aromatic Nitroreductions - Rahman, MD Taifur; Wharry, Scott; Smyth, Megan; Manyar, Haresh; Moody, Thomas S. (Synlett, 2020)
A continuous-flow packed-bed catalytic reactor has been developed for hydrogenation of aromatic nitrobenzoic acids in water to produce the corresponding anilines. These hydrogenations are green, more efficient, less consumptive, and safer than the conventional reduction process. Various industrially important aromatic amines have been produced in excellent yields and with high throughput. The optimized continuous-flow reduction process produces no detectable genotoxic intermediates, unlike the corresponding batch reduction. The reactor is modular in design and can be scaled up to produce several kilograms of product per day without extensive redesign.
Keywords: green chemistry; catalytic hydrogenation; continuous-flow packed-bed reactor; nitrobenzoic acids; anilines